Large seeds as a defensive strategy against partial granivory in the Fagaceae - Chen, Si‐Chong; Antonelli, Alexandre; Huang, Xiao; Wei, Neng; Dai, Can; Wang, Qing‐Feng (The Journal of ecology, 2025)
Large seeds interact with a wide range of animals (e.g. predators) and are dispersed via certain small animals' foraging behaviours, such as caching. Some of the most iconic species of large‐seeded plants have long fascinated ecologists studying biotic interactions, such as oaks and their relatives in the Fagaceae family. The Fagaceae acorns are dispersed through synzoochory, a specific dispersal mode in which animal partners act as both seed dispersers and granivores. Although granivory (i.e. seed herbivory) can profoundly impact the survival of plant offspring, partial damage on seed reserves is a prevalent phenomenon that does not always result in seed mortality. However, previous single‐species studies have resulted in mixed evidence across treatments and traits, leaving the impact of partial granivory on plant regeneration unclear. Using artificial granivory experiments on 1185 seeds of 20 Fagaceae species, here we quantify how partial loss of seed reserve affects seed germination, seedling growth and biomass allocation across a damage gradient from 0% to 96% biomass loss. We show that, although partial granivory reduces seedling growth (e.g. total biomass and number of leaves), it does not significantly affect seed germination or the overall biomass allocation of seedlings (e.g. leaf mass fraction and root:shoot biomass ratio). Seedlings from seeds more preyed upon have higher specific leaf area, indicating that they tend to grow larger but less protected leaves against herbivores, perhaps to compete for light. Synthesis. As seeds dispersed through scatter‐hoarding granivores have evolved relatively large sizes, like Fagaceae acorns, our findings demonstrate that this type of seeds may tolerate partial granivory in exchange for high dispersal efficiency. This study opens new perspectives to our understanding of seed size diversity and evolution. We conclude that seed size per se is a defensive trait, that large seeds counteract potential losses of seed reserve to escape full predation and allow germination. 摘要 植物的大型种子可与多种动物(如捕食者)发生相互作用，并可通过某些小型动物的觅食行为(如贮藏)实现散布。壳斗科等典型的大种子植物因其种子与其它生物的互作特性，长期以来吸引着生态学家的广泛关注。 壳斗科植物的种子以一种特殊的动物体外传播模式进行扩散，在这一过程中，动物既是传播者又是捕食者。尽管动物取食种子(即种子捕食)会显著影响植物后代的存活，但种仁部分受损却不致死的现象非常普遍。然而，先前的单一物种研究在不同实验处理和性状上的结果不一致，使得种子部分损坏对植物更新的具体影响尚未明确。 本研究通过模拟种子捕食实验，对20种壳斗科植物的1,185颗种子进行了研究，量化了种仁部分受损(生物量损失从0%到96%不等)对种子萌发、幼苗生长及生物量分配的影响。 结果表明，尽管种仁部分受损会降低幼苗生长(如总生物量和叶片数量)，但对种子萌发和幼苗整体的生物量分配(如叶重量比、根茎比)并无显著影响。由受损程度较高的种子萌发出的幼苗通常具有更高的比叶面积，倾向于长出更大但防御性较低的叶片，以此在光照竞争中占据优势。 综上所述，壳斗科等通过动物分散贮藏传播的植物进化出了相对较大的种子，这类种子可能通过容忍种仁部分受损来换取更高的传播效率。本研究为种子大小的多样性与进化提供了新视角，表明种子大小本身是一种防御性特征，较大的种子能够抵消种仁部分损失的后果，避免被完全取食，从而确保萌发和后代的成功建立。 Large seeds dispersed by scatter‐hoarding granivores, such as Fagaceae acorns, tolerate partial damage to achieve higher dispersal efficiency. By demonstrating that seed size itself acts as a defensive trait, the findings provide new insights into seed size diversity and evolution, highlighting how large seeds counterbalance reserve losses to evade full predation and ensure germination.